2021
DOI: 10.1111/jvim.16239
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a commercially available thymidine kinase 1 assay for diagnosis of lymphoma in 42 hospitalized horses (2017‐2020)

Abstract: Background Antemortem definitive diagnosis of lymphoma in horses is often difficult. Thymidine kinase 1 (TK1) assay is a potentially useful biomarker for lymphoma in horses. Hypothesis/objectives To report the clinical performance of a commercially available TK1 assay for diagnosis of lymphoma in horses. We hypothesized that there would be no association between serum TK1 activity and a diagnosis of lymphoma in horses. Animals Forty‐two hospitalized horses, 14 with a definitive diagnosis of lymphoma, 4 with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
8
1
7
Order By: Relevance
“…There is a high production of this enzyme in fast‐proliferating neoplastic cells, and increased serum activity is caused by the leakage of TK1 after their death (Hallek et al., 1992 ); thus, the TK1 activity in serum correlates with the proliferative activity of the tumour (Hallek et al., 1992 ). However, the enzyme is highly unspecific as it can be released from many cells, including hepatocytes, hematopoietic and various neoplastic cells (Moore et al., 2021 ; Tanaka et al., 1993 ).…”
Section: Enzymesmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a high production of this enzyme in fast‐proliferating neoplastic cells, and increased serum activity is caused by the leakage of TK1 after their death (Hallek et al., 1992 ); thus, the TK1 activity in serum correlates with the proliferative activity of the tumour (Hallek et al., 1992 ). However, the enzyme is highly unspecific as it can be released from many cells, including hepatocytes, hematopoietic and various neoplastic cells (Moore et al., 2021 ; Tanaka et al., 1993 ).…”
Section: Enzymesmentioning
confidence: 99%
“…Inflammatory diseases cause a temporary elevation in TK1 activity in humans and dogs, most probably due to the proliferation of the leucocytes and their lysis at the site of inflammation (Gronowitz et al., 1983 ; Nakamura et al., 1997 ). A modest increase in the serum activity of TK1 was detected in a few horses with various inflammatory conditions (Larsdotter et al., 2015 ; Moeller et al., 2020 ; Moore et al., 2021 ).…”
Section: Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated levels of PTH-related peptide (PTH-rP) were reported in one horse affected with multiple myeloma (Barton et al, 2004). Although elevated serum thymidine kinase-1 (TK1) levels have been proposed as useful diagnostic indicators of lymphoma in horses (Larsdotter et al, 2015), later studies yielded conflicting results (Moore et al, 2021;Wang et al, 2021). Although the authors concluded that a paraneoplastic explanation for hypercalcemia could be ruled out based on a normal TK1 level in their patient, caution in that regard is recommended until better cancer biomarkers with improved positive and negative predictive values have been evaluated and validated for both equine and human medicine.…”
mentioning
confidence: 99%